2017
DOI: 10.3390/rs9121303
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Seasonal Crustal Motion in Tianshan Area Using GPS, GRACE and Surface Loading Models

Abstract: Abstract:Complex tectonic and non-tectonic movements exist in the Tianshan area. However, we have not acquired good knowledge of such movements yet. In this study, we combine Global Positioning System (GPS), the Gravity Recovery and Climate Experiment (GRACE) and Surface Loading Models (SLMs) data to study the seasonal vertical crustal displacements in the Tianshan area. The results show that all three datasets exhibit significant annual variations at all 26 local GPS stations. Correlation coefficients higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Moreira et al (2016) showed that the deviation between the monthly vertical component of GPS and GRACE was smaller than that of the global hydrological model among the 18 GPS stations of the Amazon basin, although the root mean squares (RMS) variation of the GPS series accounts for up to 70 %. Wu et al (2017) found that the seasonal crustal vertical deformation measured by GPS was more consistent with the results obtained by SLMs than GRACE, in the Tianshan area, and the correlation was better, mainly due to the influence of the atmospheric load. For the European region, some scholars have not combined GPS, GRACE and the hydrological model, and the load data sources used are different (e.g., Van Dam et al, 2007;Ma, 2017).…”
Section: Introductionsupporting
confidence: 74%
“…Moreira et al (2016) showed that the deviation between the monthly vertical component of GPS and GRACE was smaller than that of the global hydrological model among the 18 GPS stations of the Amazon basin, although the root mean squares (RMS) variation of the GPS series accounts for up to 70 %. Wu et al (2017) found that the seasonal crustal vertical deformation measured by GPS was more consistent with the results obtained by SLMs than GRACE, in the Tianshan area, and the correlation was better, mainly due to the influence of the atmospheric load. For the European region, some scholars have not combined GPS, GRACE and the hydrological model, and the load data sources used are different (e.g., Van Dam et al, 2007;Ma, 2017).…”
Section: Introductionsupporting
confidence: 74%
“…Zou et al (2016) focused on the seasonal variation in the horizontal and vertical movements of southern Tibet by performing a joint analysis of GPS and GRACE data, and found that GPS-derived and GRACEderived seasonal oscillations are in good agreements. Wu et al (2017) investigated the seasonal crustal movements in Tianshan area using GPS, GRACE, and Surface Loading Models (SLMs), and confirmed that the consistency between the GPS and SLMs data was higher, which is probably due to the dominant atmospheric loading effects in this region. Li et al (2019) investigated the surface seasonal mass changes and vertical crustal deformation in North China using the measurements of GPS and GRACE.…”
Section: Grace Datamentioning
confidence: 83%
“…However, the data sets of GRACE and LSDM exhibit better consistency at most sites, as evidenced by the fact that the displacement time series of GRACE fits that of LSDM better. The main reason for the difference is that GRACE and LSDM represent smooth results limited by spatial resolution, while GPS observations are more sensitive to local effects (Wu et al, 2017). Figure 2 depicts the comparison of three data sets at sites SCXC and YNZD situated in Sichuan and Yunnan province, respectively.…”
Section: Comparison Of Deformations Derived From Three Techniquesmentioning
confidence: 99%
“…The strongest recorded event was the M s 6.0 earthquake that struck in 1934 (Shen and Song 2008). Recent GPS measurements indicated that the compressional deformation of the Tianshan area is accommodated primarily by a series of W-E-trending fold-thrust belts with a slip rate of 1-2 mm/a and that Urumqi is moving toward the NE at a rate of 4-5 mm/a (Yang et al 2008;Wu et al 2017). The city is currently characterized by moderate to low seismic activity, and no major earthquake has occurred recently.…”
Section: Study Areamentioning
confidence: 99%